Developing an online laundry service quality framework - Hana Afifah (2019)
The purpose of this study was to explore the customers' assessment and thedimensions that influence customers' purchase and repurchase intention of LarasOnline Laundry Service in order to develop the online laundry service qualityframework. A qualitative research design with a single-case study approach wasemployed to answer the research questions. The conceptual framework of this studywas based on the theory of E-S-QUAL developed by Parasuraman, Zeithaml, andMalhotra. Twenty nine customers were selected as a sample by purposive samplingmethod. All of the participants were interviewed face-to-face by the researcher. Theresearcher conducted the observation of the online laundry service in actual settingand collected the documents of Laras Laundry as part of the data collection. Thematicanalysis on the interview data was performed by using ATLAS.ti to identify the themeemerged from the data. The result showed that the online laundry service qualityframework consist of eight dimensions namely (1) easy and flexible, (2) fast, (3)hygiene, tidy, and fragrant, (4) trustworthy, (5) friendly employee, (6) reliable andresponsive, (7) personality and social network, and (8) effective and efficient, whichinfluenced customers' purchase and repurchase intention. In conclusion, the empiricaldata confirmed the eight dimensions that are critical in developing a quality onlinelaundry service framework. The implication of this study is the introduction of theeight dimensions of the framework into the current online laundry service, whichcould enhance their service quality and grow their business.